2004
DOI: 10.1159/000079839
|View full text |Cite
|
Sign up to set email alerts
|

French Version of the Addiction Severity Index (5th Edition): Validity and Reliability among Swiss Opiate-Dependent Patients

Abstract: Objective: The aim of the study was to validate a French adaptation of the 5th version of the Addiction Severity Index (ASI) instrument in a Swiss sample of illicit drug users. Participants and Setting: The participants in the study were 54 French-speaking dependent patients, most of them with opiates as the drug of first choice. Procedure: Analyses of internal consistency (convergent and discriminant validity) and reliability, including measures of test-retest and inter-observer correlations, were conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
2
16
0
3
Order By: Relevance
“…-ASI [3,14,15] . ASI is an interview that assesses history, frequency and consequences of alcohol and drug use.…”
Section: Methodsmentioning
confidence: 99%
“…-ASI [3,14,15] . ASI is an interview that assesses history, frequency and consequences of alcohol and drug use.…”
Section: Methodsmentioning
confidence: 99%
“…We considered this design a 10 Previously existing trends persist. 11 In a pre-post design the tendency is found that the follow-up values are again situated closer to the mean, because random error in the pre-measurement possibly caused a proportion of the extreme values. 12 Improvement occurs spontaneously and does not stem from the judicial intervention.…”
Section: Measurementmentioning
confidence: 98%
“…As a consequence, we can see that a lot of differences exist in the way this progress is measured in several studies. 5 We based our choice of the life spheres and the criteria for improvement mainly on the EuropASI-instrument, which is used as an assessment instrument for clients of drug treatment services [11]. We thus studied drug use, financial situation, housing, social and family relationships and leisure time.…”
Section: Measurementmentioning
confidence: 99%
“…However, all addicted patients are not equally severely affected and a dimensional addiction severity scale has been developed to assess general behavioural, health and social drug-induced impairments (45)(46)(47)(48)(49).…”
Section: What Is Drug Addiction?mentioning
confidence: 99%